Effect and mechanism analysis of resonance on physical parameters of unconventional reservoirs. (November 2022) - Kang, Zhongjian; Gao, Chong; Gong, Dajian; Zhai, Gangyi; Wang, Yufang; Du, Haoran
Abstract: Inducing shale reservoir resonance is an environmentally friendly and efficient unconventional oil/gas production technology. It is necessary to study the effect of resonance on shale physical parameters. This paper clarifies the resonance mechanism of improving shale reservoirs and constructs the natural frequency parameter equation under a single excitation direction using vibration system theory and rock mechanics. The resonance experiment is carried out after the physical parameters of the shale and coal samples are verified by material characterization technology. Meanwhile, CT scanning technology and matrix permeability tests are used to measure the samples' pore development and permeability changes. Eventually, the coalbed methane field in Qinshui Basin, Shanxi province, was selected as the experimental object for the reservoir resonance test. We analyzed the production data of the test wellhead. The results indicate that the mechanism of resonance improvement of shale physical parameters promotes the redevelopment of primary cracks in the rock mass; the porosity and permeability of rock mass are increased by 2–12 times and 2–8 times, respectively, after the once resonance test. The CBM (coalbed methane) wells whose productivity is in a state of decay have been significantly enhanced after resonance stimulation, and the relative daily gas production is increased by 101.61%. Highlights: Clarify the mechanism of resonance reconstruction of unconventional reservoirs. Constructed the mathematical model of natural frequency and resonance condition. Sample's porosity and permeability increase 2–12 times and 2–8 times respectively. The CBM well's average daily gas production increases 101.61% after resonance. Resonance reconstruction of unconventional reservoirs is suitable in actual application.